DESAIN SIKAT LANTAI MULTIFUNGSI DENGAN GAGANG - Hotman Fery Siregar (Universitas Mercu Buana, 2021)
The floor brush is one of the hygiene products that are still a mainstay for cleaning floors, bathroom walls and other hard surfaces. Floor brushes in its use still not fully pay attention to aspects of user needs, such as user convenience and functionality. The use of floor brushes is mostly done in an abnormal work position, such as brushing the floor with a squatting position or with a bent position. With method starting from the stage of extracting ideas, the analysis continues with the development stage, design concepts, systems and details, prototyping, production processes, product evaluation or testing, ending with the distribution stage. Evaluation also needs to use certain benchmarks, to find out how far a design has met the technical, functional, aesthetic and economic quality. Cleaning activities are needed for a certain period to maintain the area where the activity becomes more comfortable. Bathroom or toilet is the most crucial room for a dwelling. Required hygiene tool that has more functionality than just brush the floor (multifunction), and also compact, so it can do efficient use of equipment cleanliness and ease in use.